(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: India faces a critical organ shortage with only 0.8 donors per million population. Healthcare workers play a pivotal role in organ donation, yet their knowledge and attitudes in rural settings remain understudied. Objective: To assess knowledge, attitude, and perception regarding cadaveric organ donation among healthcare workers at KIMS, Koppal, and determine their willingness toward organ donation. Methods: Cross-sectional survey conducted among 1,000 healthcare professionals (275 doctors, 404 nurses, 321 support staff) at KIMS Koppal between August 2024-July 2025 using structured questionnaire. Data analyzed using SPSS 20.0 with chi-square test for associations. Results: Overall willingness for organ donation was 68.7%, significantly higher among doctors (78.2%) compared to nurses (69.8%) and support staff (59.2%) (p<0.001). While 73.1% correctly identified brain-dead patients as ideal donors and 71.1% knew ICU as declaration site, significant gaps existed: only 20.8% knew about heart valve donation and 45% incorrectly believed age limits donation. Personal connection with donors significantly increased willingness (83.1% vs 62.3%, p<0.001). Internet (39.7%) was the primary information source. Conclusion: Healthcare workers demonstrate reasonable foundational knowledge but substantial gaps persist regarding comprehensive organ donation knowledge and age-related misconceptions. Targeted educational interventions and awareness campaigns featuring personal testimonials can enhance donation rates in rural tertiary care settings.